Composition, stability and electrolyte permeability of Golgi membranes from lactating-rat mammary gland. - White, M D (1981)
1. Golgi membrane vesicles, isolated from lactating-rat mammary gland and greatly enriched in galactosyltransferase (EC 2.4.1.22), contained over 40 separate bands of protein, including some periodic acid)(Schiff-staining material and free thiol groups, when analysed by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. 2. The membrane lipids were enriched in phosphatidylcholine, phosphatidylethanolamine and unesterified cholesterol. 3. Membrane fluidity, as monitored by the fluorescence polarization of 1,6-diphenylhexa-1,3,5-triene, increased linearly over 5-37 degrees C. 4. The vesicle membranes were impermeable to lactose over a wide pH range, but admitted electrolytes of molecular weight below about 300. 5. These properties are discussed with respect to other cellular membranes and the secretion of milk products.